A simple formulation for effective flexural stiffness of circular reinforced concrete columns. (February 2015) - Caglar, Naci; Demir, Aydin; Ozturk, Hakan; Akkaya, Abdulhalim
Abstract: Concrete cracking reduces flexural and shear stiffness of reinforced concrete (RC) members. Therefore analyzing RC structures without considering the cracking effect may not represent actual behavior. Effective flexural stiffness resulting from concrete cracking depends on some important parameters such as confinement, axial load level, section dimensions and material properties of concrete and reinforcing steel. In this study, a simple formula as a securer, quicker and more robust is proposed to determine the effective flexural stiffness of cracked sections of circular RC columns. This formula is generated by genetic programming (GP). The generalization capabilities of the explicit formulations are compared by cross sectional analysis results and confirmed on a 3-D building model. Moreover the results from GP based formulation are compared with EC-8 and TEC-2007. It is demonstrated that the GP based model is highly successful to determine the effective flexural stiffness of circular RC columns.